"Walking on Eggshells:" A Qualitative Study of How Friends of Young Women Experiencing Intimate Partner Violence Perceive Their Role - McKenzie, Mandy (Journal of interpersonal violence, 2022)
Young women who experience intimate partner violence (IPV) are most likely to turn to their friends for help. Although friends can play a critical role in providing support, there is little research that examines friends? experiences. In this qualitative study, we explored how friends of young women experiencing IPV perceived their role in responding to IPV in the context of friendship. We held in-depth interviews with 15 friends of young women who had experienced IPV and used reflexive thematic analysis to develop key themes from the data. We developed two overarching themes that reflected participants? perceptions of the roles they had played or considered as a friend in responding to IPV: ?taking action? (which included ?providing an outsider?s view,? ?being an advisor or coach,? ?being a protector,? and ?taking a stand?); and ?being there? (which included ?being a listener,? ?being a companion? and ?being an ally?). Their perceptions were shaped by friendship expectations, as well as by understandings of IPV. However, deciding what role to play in supporting their friend was constructed as challenging due to conflicting expectations that arose in the context of friendship. It involved balancing a perceived responsibility to do what they thought was best for their friend?s well-being, a need to promote honesty and mutuality in the friendship, along with a competing obligation to respect their friend?s choices, maintain her trust and ensure equality in the friendship. Being friends with the abuser as well as with the victim created additional complexities. Based on our findings, we identify key areas to address in developing interventions to assist friends to respond to young women experiencing IPV. These could guide friends on how to play an effective support role while also maintaining the friendship and managing the significant emotional impacts of providing help.